2018
DOI: 10.1038/s41598-018-21667-5
|View full text |Cite
|
Sign up to set email alerts
|

Structure based function-annotation of hypothetical protein MGG_01005 from Magnaporthe oryzae reveals it is the dynein light chain orthologue of dynlt1/3

Abstract: Magnaporthe oryzae is a model fungal plant pathogen employed for studying plant-fungi interactions. Whole genome sequencing and bioinformatics analyses revealed that this fungal pathogen has more than 12,000 protein-coding genes with 65% of the genes remaining functionally un-annotated. Here, we determine the structure of the hypothetical protein, MGG_01005 and show that it is the Magnaporthe oryzae Dynein light chain Tctex-type 1 (dynlt1/3), demonstrated by its structural similarity to other orthologous dynlt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…Immunolocalization revealed a cytoplasmic staining pattern ( Fig. 5 D-F) that was consistent with the function of its fungal protein analog, dynein light chain, which is involved in intracellular transport ( Li et al, 2018 ). We also showed that invasive CTBs express CNR1.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Immunolocalization revealed a cytoplasmic staining pattern ( Fig. 5 D-F) that was consistent with the function of its fungal protein analog, dynein light chain, which is involved in intracellular transport ( Li et al, 2018 ). We also showed that invasive CTBs express CNR1.…”
Section: Discussionsupporting
confidence: 54%
“…High placental levels of this mRNA (ENSG00000163633) have been reported ( Fagerberg et al, 2014 ). Its fungal protein analog (MGG_01005) is dynein light chain Tctex-type 1 (dynlt1/3; Li et al, 2018 ), which transports various types of cellular cargo. CYP19A1 (aromatase) and GH2 (growth hormone 2) were also expressed at higher levels in the syncytium.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is unclear as yet which, if any, of these mechanisms regulates the beating of the axoneme. As indicated in Figure 5c, specific dynein subsets are perhaps activated during travel of the bend [116]. However, these models do not assign any particular conformational states to dyneins within straight or curved regions.…”
Section: In the Axoneme: Conversion Of The Shear Between Doublets Into The Bendmentioning
confidence: 92%
“…Therefore, we expect to annotate more proteins if we use protein structure in the annotation process. Some studies have successfully used protein structures to annotate the domains of protein that couldn’t be annotated by sequence alone (Bartas et al, 2022; Li et al, 2018; Zarembinski et al, 1998). However, these approaches have not been widely adopted because it is difficult to experimentally determine the structure of a protein with an unknown function.…”
Section: Introductionmentioning
confidence: 99%